RANCANG BANGUN DAN UJI TEKNIS ALAT PEMBERSIH TIPE AYAKAN DIPASANGKAN PADA MESIN PERONTOK KEDELAI MPT001 - Reyfhel H. F. Tagah; Dedie Tooy; Lady C. Ch. E. Lengkey (COCOS, 2022)
Abstract Soybean (Glycine max (L.) is a food commodity that produces vegetable protein which is very important, both because of its nutritional content, safe for consumption, and price compared to animal protein sources. Sifting is the separation of a mixture of solid particles that have various sizes of materials using a sieve. The sieving process is also used as a cleaning tool, separator of impurities whose size is different from the raw material. The purpose of the study this is the design and technical test of a sieve type cleaning device mounted on a soybean thresher machine MPT001. This research has been carried out in a home workshop and includes the manufacture of a sifter, sifting experiments and data analysis of research results. This research includes design and technical testing of cleaning equipment sieve type, Sieve device Soybeans are designed and manufactured to help farmers speed up the threshing process. Tests in the field using soybeans that are still in the stove were carried out for 3 repetitions and obtained: The average cleaning efficiency is 0.41%, and the average cleaning capacity is 33,19 kg/hour. The number of threshing results for each replication was an average of 1.7 kg. An average of 5.86 kg was wasted or other foreign objects. Reduce process chain and reduce processing time. Keywords: Tool design, swaying sieve system, tool technical test